ROLES AND PERFORMANCE EXPECTANCIES OF A GLOBAL TEACHER - Feleeh L Enanoza; Ethel L. Abao (European Scientific Journal, ESJ, 2014)
Quality and excellence in the academic workplace demand an aggressive realization on the teachers' roles in the successful delivery of instruction. The 21st century educators are looked upon as globally competitive and adept in managing change. They must possess the five basic roles: transformers, facilitator, researcher, ethicist and psychological. (Salandanan 2006) Conscious of this construct, this study which was conducted in Naga District 1, City of Naga, Cebu, analysed how well the teachers' roles were carried out and how have these been affected by the physical, psychological, emotional and spiritual factors. Utilizing the Pearson Product-Moment Correlation, findings revealed that the teachers generally carried out their roles excellently. Likewise, there were significant interrelationships between and among the roles as well as the factors that affect them. Simply put, the physical, psychological, emotional and spiritual factors directly affect the successful exercise of their roles. Teachers' Performance Appraisal and interview were likewise utilized for validation and findings were then conformed. The teacher’s physical, psychological, emotional and spiritual well-being greatly affects the performance and exercise of his/her roles as facilitator, researcher, ethicist, psychological and effective teacher. Both are potent determinants towards quality and excellence, hence they have to be continually facilitated in and pursued upon by the teachers as well as the administration. A global teacher therefore carries out his/her roles meaningfully and makes education the center stage in the upliftment of a better society across nations.